Welfare in Farmed Decapod Crustaceans, With Particular Reference to Penaeus vannamei - Albalat, Amaya; Zacarias, Simão; Coates, Christopher J.; Neil, Douglas M.; Planellas, Sonia Rey (Frontiers in Marine Science, 2022)
The farming of decapod crustaceans is a key economic driver in many countries, with production reaching around 9.4 million tonnes (USD 69.3 billion) in 2018. These efforts are currently dominated by the farming of Pacific whiteleg shrimp, Penaeus vannamei, which translates into approximately 167 billion farmed P. vannamei being harvested annually. Further production growth is expected in the future and hence the need for more research into its health and welfare is required. Herein, from an extensive survey of the available literature, we scrutinise farming practices and the challenges associated with the production of P. vannamei from an animal-centric welfare perspective (1), we propose potential welfare indicators (2) and we critically review current scientific evidence of sentience in penaeid shrimp among other commercially important decapods (3), since it is plausible that in the near future not only the largest, but in fact all decapod crustaceans will receive welfare protection. This review highlights that despite the wide knowledge on crustacean stress physiology and immunology as well as disease control, still little is known about some key parameters related to the five welfare dimensions. We recommend that further research should focus on developing a systematic integrated welfare assessment encompassing all the different aspects of the crustaceans farming and life cycle up to slaughter. Furthermore, direct and indirect species-specific operational welfare indicators should be developed for all decapod crustaceans currently farmed, similar to the ones suggested in this review for P. vannamei.